Axial loading during supine MRI for improved assessment of lumbar spine: comparison with standing MRI - Jarruwat Charoensuk; Jiraporn Laothamatas; Witaya Sungkarat; Ladawan Worapruekjaru; Boonthida Hooncharoen; Khaisang Chousangsuntorn (Acta Radiologica, 2021)
BACKGROUND: There are no studies comparing the morphologic changes of lumbar spines between supine axial-loaded and 90° standing magnetic resonance imaging (MRI) examinations of patients with spinal stenosis. PURPOSE: To determine whether axial-loaded MRI using a compression device demonstrated similar morphology of intervertebral disc, dural sac, and spinal curvature as those detected by 90° standing MRI in individuals with suspected spinal stenosis. MATERIAL AND METHODS: A total of 54 individuals suspected of having spinal stenosis underwent both axial-loaded and standing MRI studies. The outcome measures included seven radiologic parameters of the lumbar spine: measures of the intervertebral disc (i.e. cross-sectional area [DA], disc height [DH], and anteroposterior distance [DAP]), dural sac (cross-sectional area [DCSA]), spinal curvature (i.e. lumbar lordosis [LL] and L1-L3-L5 angle [LA]), and total lumbar spine height (LH). RESULTS: For agreement between the two methods, intraclass correlation coefficient (ICC) ≥ 0.8 was found for all seven radiologic parameters. Supine axial-loaded MRI underestimated LL but remained correlated (ICC = 0.83) with standing MRI. Minor differences between the two methods (≤5.0%) were observed in DA, DCSA, DAP, LA, and LH, while a major difference was observed in LL (8.1%). CONCLUSION: Using a compression device with the conventional supine MRI to simulate weight-bearing on the lumbar spine generated MRI morphology, which was strongly correlated with those from a standing MRI.
Keywords: Spine and Intervertebral Disc Pathology; Cervical and Thoracic Myelopathy; Scoliosis diagnosis and treatment